Clinical Profile and Histopathological Correlation in Women Undergoing Hysteroscopy: A 5-Year Experience at a Tertiary Center - Melike Geyik Bayman; Ümmügülsüm Esenkaya (Genel Tıp Dergisi, 2026)
Aim: This study aimed to evaluate the clinical indications, diagnostic accuracy, histopathological outcomes, and safety profile of hysteroscopy in women presenting with abnormal uterine bleeding and infertility in the post-pandemic period.Materials and Methods: A retrospective observational study was conducted on 306 patients who underwent either diagnostic or operative hysteroscopy at a tertiary referral center in Türkiye between January 2020 and June 2024. Demographic characteristics, transvaginal ultrasound findings, intraoperative observations, histopathological results, and complication rates were analyzed. All procedures were performed under general or spinal anesthesia using standardized hysteroscopic techniques. Descriptive statistics were used to evaluate the clinical relevance.Results: Abnormal uterine bleeding was the most common indication for hysteroscopy (70.7%), followed by infertility (17.3%). Preoperative ultrasonography identified intrauterine abnormalities in 69.4% of patients, most commonly suspected endometrial polyps (23.4%). Histopathological evaluation confirmed endometrial polyps as the predominant lesion (69.2%), while endometrial adenocarcinoma was detected in 2.3% of cases. The overall complication rate was low (1.3%), with uterine perforation being the only adverse event. Postoperative recovery was uneventful in 98.4% of patients, and no hospital readmissions were recorded.Conclusion: Hysteroscopy is a safe, minimally invasive, and diagnostically superior modality for the evaluation and management of intrauterine pathologies. Its high diagnostic yield and low complication rate highlight its value as a first-line approach in women with abnormal uterine bleeding and infertility. Early implementation of hysteroscopy may facilitate timely diagnosis, improve reproductive outcomes, and enable the detection of endometrial malignancy at an early stage. These findings underscore the importance of integrating hysteroscopy into routine gynecological practice, particularly in the post-pandemic era.